The comparison of laparoscopy, shock wave lithotripsy and retrograde intrarenal surgery for large proximal ureteral stones - Ozturk, Ufuk; Şener, Nevzat Can; Goktug, H.N. Goksel; Gucuk, Adnan; Nalbant, Ismail; İmamoglu, M. Abdurrahim (Canadian Urological Association Journal, 2013)
Introduction: In this study we compare the success rates and complication rates of shock wave lithotripsy (SWL), laparoscopic, and ureteroscopic approaches for large (between 1 and 2 cm) proximal ureteral stones. Methods: In total, 151 patients with ureteral stones between 1 and 2 cm in diameter were randomized into 3 groups (52 SWL, 51 laparoscopy and 48 retrograde intrarenal surgery [RIRS]). The groups were compared for stone size, success rates, and complication rates using the modified Clavien grading system. Results: Stone burden of the groups were similar (p = 0.36). The success rates were 96%, 81% and 79%, respectively in the laparoscopy, SWL, and ureteroscopy groups. The success rate in laparoscopy group was significantly higher (p < 0.05). When these groups were compared for complication rates, RIRS seemed to bethe group with the lowest complication rates (4.11%) (p < 0.05). SWL and laparoscopy seem to have similar rates of complication (7.06% and 7.86%, respectively, p = 0.12). Interpretation: To our knowledge, this is the first study to compare the results of laparoscopy, SWL and RIRS in ureteral stones. Our results showed that in management of patients with upper ureteral stones between 1 and 2 cm, laparoscopy is the most successful method based on its stone-free rates and acceptable complication rates. However, the limitations of our study are lack of hospital stay and cost-effectiveness data. Also, studies conducted on larger populations should support our findings. When a less invasive method is the only choice, SWL and flexible ureterorenoscopy methods have similar success rates. RIRS, however, has a lower complication rate than the other approaches.